The Influence Of Digital Literacy On Management MSMES Finance With Financial Literacy as a Moderating Variable In East Medan District - Fitriani Saragih; Hafsah Hafsah (International Journal Of Economics Social And Technology, 2026)
This study examines the effect of digital literacy on the financial management of micro, small, and medium enterprises (MSMEs), with financial literacy serving as a moderating variable in East Medan District, Indonesia. Although digital technologies have become increasingly accessible to MSMEs, effective financial management remains a significant challenge, indicating that digital capabilities alone may not be sufficient to improve financial practices. This study conceptualizes digital literacy through social media utilization, e-commerce adoption, and digital data management, while MSME financial management is reflected in financial recordkeeping, budgeting, cash flow control, and basic financial reporting. A quantitative research approach was employed using a survey of 120 MSME owners selected through purposive sampling, and the data were analyzed using Moderated Regression Analysis (MRA). The findings demonstrate that digital literacy positively influences MSME financial management. Furthermore, financial literacy strengthens the relationship between digital literacy and financial management, indicating that MSME owners with higher levels of financial literacy are better able to transform their digital competencies into effective financial management practices. These findings highlight the complementary roles of digital and financial literacy in supporting sustainable MSME development and suggest that capacity-building programs should integrate both competencies to enhance MSME competitiveness in the digital economy.